PENAMPINGAN DAN PELATIHAN GAYA KEPEMIMPINAN APARAT DESA DI KECAMATAN SUMBANG, KABUPATEN BANYUMAS BERBASIS BUDAYA - Adi Indrayanto; Wita Ramadhanti; Zuhdan Ali Hudaya; Solehan Solehan (Sinergi Abdimas Jurnal Pengabdian Masyarakat, 2024)
Village Government is the smallest formal government authority in Indonesia that have their own financial budget. Majority of Indonesia citizen lives in villages. Distinct from head of the villages that choose democratically by villages’ citizen, village government officer is administrative position that coordinates the project in the villages. This community development program objectives are teaching and mentoring the villages’ officer in Sumbang Distric, Banyumas County. This community development using teaching and mentoring method. The participants are asked to filled the test to find out their leadership style using “Managerial Grid” method. The community development team then appraise their test results and announce to the participants. Participants then teach about the leadership style and how to manage it to attain optimal results. Sumbang district has 19 Villages, each are asked to send their 2 officer, villages’ secretary and villages head of finance. Based on the test, majority of the participants are classified as “Team leader”. Furthermore, the participants then taught about types of leadership style and how to optimized it based on their tasks.